Unlocking emotional engagement: How Tiktok live streaming transforms customer-brand relationships in the digital era - Daffah, Mohamad Iqbal; Kusumawati, Andriani; Wiyata, Wiyata (Bricolage : Jurnal Magister Ilmu Komunikasi, 2024)
The lack of understanding about how live streaming on social media platforms like TikTok can build emotional engagement between customers and brands and the factors influencing such engagement in the era of the fourth industrial revolution led to this research. Using the Uses and Gratification (U&G) Theory to explain the motivations behind media use in fulfilling social and psychological needs, along with the Theory of Reasoned Action (TRA), which emphasizes attitudes as the primary determinants of behavior, the objective of this study is to analyze the influence of gratification, media attributes, and perceived interactivity on attitudes towards live streaming and brand attitudes, as well as the impact of these attitudes on consumer engagement. This explanatory research employs a quantitative approach, with a sample of 250 consumers of the Kattoen brand on TikTok selected through purposive sampling. The data are analyzed using descriptive and inferential statistics through Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique. The research instrument is an online questionnaire that has been validated and reliably tested. The results show that gratification does not have a significant effect on attitudes toward live streaming, while media attributes and perceived interactivity have a significant effect on both intervening variables, namely attitudes toward live streaming and attitudes toward the brand. These findings indicate that media elements and interactivity play an important role in shaping positive consumer attitudes toward live streaming and the brand, ultimately increasing consumer engagement in TikTok live streaming.